Lesion Material From Treponema-Associated Hoof Disease of Wild Elk Induces Disease Pathology in the Sheep Digital Dermatitis Model - Wilson-Welder, Jennifer H.; Mansfield, Kristin; Han, Sushan; Bayles, Darrell O.; Alt, David P.; Olsen, Steven C. (Frontiers in Veterinary Science, 2022)
A hoof disease among wild elk (Cervus elaphus) in the western United States has been reported since 2008. Now present in Washington, Oregon, Idaho and California, this hoof disease continues to spread among elk herds suggesting an infectious etiology. Causing severe lesions at the hoof-skin junction, lesions can penetrate into the hoof-horn structure causing severe lameness, misshapen hooves, and in some cases, sloughed hooves leaving the elk prone to infection, malnutrition and premature death. Isolated to the feet, this disease has been termed treponeme-associated hoof disease due to the numerous Treponema spp. found within lesions. In addition to the Treponema spp., treponeme-associated hoof disease shares many similarities with digital dermatitis of cattle and livestock including association with several groups of anaerobic bacteria such as Bacteroides, Clostridia, and Fusobacterium, neutrophilic inflammatory infiltrate, and restriction of the disease to the foot and hoof tissues. To determine if there was a transmissible infectious component to this disease syndrome, elk lesion homogenate was used in a sheep model of digital dermatitis. Ten animals were inoculated with lesion material and lesion development was followed over 7 weeks. The majority of inoculated feet developed moderate to severe lesions at 2- or 4-weeks post-inoculation timepoints, with 16 of 18 feet at 4-weeks also had spirochetes associated within the lesions. Histopathology demonstrated spirochetes at the invading edge of the lesions along with other hallmarks of elk hoof disease, neutrophilic inflammatory infiltrates and keratinocyte erosion. Treponema-specific PCR demonstrated 3 phylotypes associated with elk hoof disease and digital dermatitis were present. Serum of infected sheep had increased anti-Treponema IgG when compared to negative control sheep and pre-exposure samples. Analysis of the bacterial microbiome by sequencing of the bacterial 16S rRNA gene showed a community structure in sheep lesions that was highly similar to the elk lesion homogenate used as inoculum. Bacteroidies, Fusobacterium and Clostridia were among the bacterial taxa overrepresented in infected samples as compared to negative control samples. In conclusion, there is a highly transmissible, infectious bacterial component to elk treponeme-associated hoof disease which includes several species of Treponema as well as other bacteria previously associated with digital dermatitis.